2013
DOI: 10.1364/oe.21.009198
|View full text |Cite
|
Sign up to set email alerts
|

Formation and evolution mechanisms of plasmon-induced transparency in MDM waveguide with two stub resonators

Abstract: We demonstrate the realization of plasmonic analog of electromagnetically induced transparency (EIT) in a system composing of two stub resonators side-coupled to metal-dielectric-metal (MDM) waveguide. Based on the coupled mode theory (CMT) and Fabry-Perot (FP) model, respectively, the formation and evolution mechanisms of plasmon-induced transparency by direct and indirect couplings are exactly analyzed. For the direct coupling between the two stub resonators, the FWHM and group index of transparent window to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 24 publications
4
42
0
1
Order By: Relevance
“…2(g), the coupling-out field C 1 nearly has a ~π phase difference with C 2 , which leads to the transparent response [35]. Therefore, the EIT-like optical response results from destructive interference between TM 11 and TM 02 modes through the MDM bus waveguide, which is similar to the formation mechanisms of PIT in previously reported coupled-resonator structures [6,8,11,14,20]. Slow light is one of the most important applications for EIT effect in atom systems, and the plasmonic system also supports slow group velocities [8,20,34].…”
Section: Simulation Results and Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…2(g), the coupling-out field C 1 nearly has a ~π phase difference with C 2 , which leads to the transparent response [35]. Therefore, the EIT-like optical response results from destructive interference between TM 11 and TM 02 modes through the MDM bus waveguide, which is similar to the formation mechanisms of PIT in previously reported coupled-resonator structures [6,8,11,14,20]. Slow light is one of the most important applications for EIT effect in atom systems, and the plasmonic system also supports slow group velocities [8,20,34].…”
Section: Simulation Results and Discussionsupporting
confidence: 62%
“…Surface plasmon polaritons (SPPs) trapped on the metal-dielectric interface can break the classical diffraction limit and manipulate light in the nanoscale domain [25-32]. Among various plasmonic guiding structures, MDM waveguides, which are easily fabricated and have deep subwavelength confinement of light with an acceptable propagation length for SPPs, have attracted much attention [5,8,14,20,21,28,32]. Based on the unique feature of MDM waveguide, the analog of EIT observed in the coupled optical resonator systems was theoretically predicted and experimentally demonstrated in recent research [5-9, 11, 13, 14, 20-23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, these researches mainly focused on the sensors' performance numerically, the further sensing optimization based on analytical model is seldom discussed. In addition, many reports revealed that the PIT effect can also be realized in NCMDM waveguide systems [15][16][17][18]. From the above discussion, we think that the PIT waveguide system is an ideal candidate for the integrated plasmonic sensor.…”
Section: Introductionmentioning
confidence: 83%
“…Lately, the nanoresonator-coupled metal-dielectric-metal (NCMDM) waveguide structure, with advantages of easy fabrication, light manipulation and convenient integration, has also been found available for the sensor research [13][14][15]. Lu et al reported a plasmonic sensor in a waveguide system and got a figure of merit (FOM) of ~500 [13], and Qi et al also observed a sensing phenomenon in the MDM waveguide structure and achieved FOMs over 650 [14].…”
Section: Introductionmentioning
confidence: 99%